ACTUATING MANAGEMENT OF MUMARASAH ‘ARABIYAH PROGRAM TO IMPROVE LANGUAGE SKILL AT IMAM BONJOL PADANG STATE ISLAMIC UNIVERSITY - Hasibuan, Renni; Khair, Miftahul (Riyahuna: Jurnal Pendidikan Bahasa Arab, 2025)
To improve students' language skills, Student Association Of Arabic Education Study Program took the initiative to implement a program called Mumarasah al-'Arabiyah. As for the program must be managed by good actuating management in three aspects, leadership, communication and supervision. Therefore, this research aims to analyze and discribe the actuating management of Mumarasah al-'Arabiyah program implemented by Arabic Education students at Imam Bonjol State Islamic University Padang, which focuses on three aspects, leadership, communication and supervision. The type of research is qualitative  with descriptive methods, with in information collected from Student Association of Arabic Education Study Program by interview and observation technique. Then data analysis used Miles and Huberman analysis model with the following steps: data collection, data reduction, data display, and conclusion drawing. The research results are : 1) The Mumarasah al-'Arabiyah program has been implemented well, this is indicated by implemented 3 aspects (leadership, communication, supervision) of implementation management well, 2) The leadership style is mixed leadership, between democratic and autocratic, 3) The communication applied in three systems: top down communication, bottom up communication, and horizontal communication, 4) The supervision applied by inviting Arabic Education lecturers to attend the Mumarasah al-Arabiyah activities and then provide the improvments, like the hiwar material that was presented was too long, there was a lack of oversight from the committee, or even the suggestion that interesting activities be carried out during mumarasah events, such as occasional mumarasah activities being outdoors.